(untitled) (Philology, 2022)
The text examines selected comic moments from Plautus’ comedy Menaechmi with a main focus on verbal humor and the translation of those excerpts into Bulgarian in Alexander Nichev’s translation. The translation model of Jean-Paul Vinay and Jean Darbelnet with its strategies and procedures is applied to each of the cited examples, briefly examining the relationships between its structural elements and illustrating what entail those among them, necessary for this analysis. The study’s purpose is to establish to what extent this model, with its great influence in the field of translation studies and its hierarchical structure, is applicable to the translation of verbal humor and which aspects of comic display remain possibly unattainable for transfer into the target language and culture and for what reason.